2011
DOI: 10.1159/000331864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thymol on Ca<sup>2+</sup> Homeostasis and Viability in MG63 Human Osteosarcoma Cells

Abstract: Aims: The effect of the natural product thymol on cytosolic Ca2+ concentrations ([Ca2+]i) and viability in MG63 human osteosarcoma cells was examined. Methods: The Ca2+-sensitive fluorescent dye fura-2 was applied to measure [Ca2+]i. Results: Thymol at concentrations of 200–1,000 µmol/l induced a [Ca2+]i rise in a concentration-dependent fashion. The response was decreased partially by removal of extracellular Ca2+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…Mast cell degranulation and histamine production is Ca 2+ dependent and thymol has previously been shown to mobilize calcium stores in glioblastoma, 29 osteoblastoma, 31 and pituitary GH3 cells. 30 To test whether thymol directly affects mast cell Ca 2+ flux, BMMCs were load with fluo-4-AM and analyzed by flow cytometry before and after thymol stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cell degranulation and histamine production is Ca 2+ dependent and thymol has previously been shown to mobilize calcium stores in glioblastoma, 29 osteoblastoma, 31 and pituitary GH3 cells. 30 To test whether thymol directly affects mast cell Ca 2+ flux, BMMCs were load with fluo-4-AM and analyzed by flow cytometry before and after thymol stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…28 Despite this very early clinical report, the use of thymol in treating skin inflammation has not been further pursued, perhaps because the underlying mechanisms are unknown. Studies investigating the effect of thymol in vitro have shown that low thymol concentrations of can promote calcium mobilization 29-31 and protect cells from DNA damage, 32, 33 radiation-induced cytotoxicity, 25 and oxidative stress. 34 Conversely, at higher concentrations, it inhibits cell proliferation and can induce apoptosis in human and murine cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer effect of thymol on various cancers has been reported (20)(21)(22)(23)(24). However, the effect of thymol on the motility of glioma cells…”
Section: Discussionmentioning
confidence: 99%
“…Permeabilization of outer and inner mitochondrial membranes leads to cell death by apoptosis and necrosis [71, 72]. Apoptosis induced by thymol in cancer cells was associated with mitochondrial pathway [73, 74]. TUNEL assay revealed that thymol and essential oils of T. vulgaris and O. vulgare can induce apoptosis in the cells of protoscoleces.…”
Section: Discussionmentioning
confidence: 99%